Management of poisoning: general protocol - Reddenna, Languluri; Krishna, Tedlla Rama (International Journal of Pharmacology and Toxicology, 2013)
Poisons used for many purposes across the duration of human existence, most commonly as weapons, anti-venoms, and medicines. Poison had allowed much progress in branches, toxicology, and technology, among other sciences and discovered in ancient times, used by ancient tribes and civilizations as a hunting tool to quicken and ensure the death of their prey or enemies.Poisons are substances, whichcause disturbances to organisms, usually by chemical reaction or other activity on the molecular scale, when a sufficient quantity is absorbed by an organism. Poisons are of diverse natures because they are classified by origin, physical form, chemical nature, chemical activity, target site, or use. For example, it was estimated that deliberate ingestion of pesticides causes 370,000 deaths each year.Poison Control Centers answer questions about potential poisons in addition to providing treatment management advice about household products, medicines, pesticides, plants, bites and stings, food poisoning, and fumes.